Ion Beam Techniques and Applications - Ahmad, Ishaq; Zhao, Tingkai (IntechOpen, 2020)
A wide variety of ion beam techniques are being used in several versatile applications ranging from environmental science, nuclear physics, microdevice fabrication to materials science. In addition, new applications of ion beam techniques across a broad range of disciplines and fields are also being discovered frequently. In this book, the latest research and development on progress in ion beam techniques has been compiled and an overview of ion beam irradiation-induced applications in nanomaterial-focused ion beam applications, ion beam analysis techniques, as well as ion implantation application in cells is provided. Moreover, simulations of ion beam-induced damage to structural materials of nuclear fusion reactors are also presented in this book.